Ascorbate ameliorates Echis coloratus venom-induced oxidative stress in human fibroblasts - Al-Sheikh, Yazeed A. (Exp Ther Med, 2017)
Reports related to the effects of Echis coloratus venom (EcV) on the antioxidant capacity of human tissues is very scarce. The present study was undertaken to investigate the activities and gene expression levels of glutathione peroxidase (GPx), glutathione reductase (GR), glutathione S-transferase (GST), superoxide dismutase (SOD) and catalase (CAT), as well as the levels of reduced glutathione (GSH), oxidized glutathione (GSSG) and the generation rates of superoxide anions (SOA), hydrogen peroxide (H(2)O(2)) and lipid peroxides (LPO) in cultured human fibroblasts incubated with EcV, ascorbate (Asc) and EcV plus Asc at concentrations and incubation periods that maintained cell viability. Results indicated that the activities of all antioxidant enzymes and their corresponding transcripts underwent highly significant decreases and downregulation in EcV-treated cultures (0.5 µg/ml medium for 4 h) compared to venom-free controls (P<0.001). Additionally, there were concurrent equally significant increases in SOA, H(2)O(2) and LPO generation rates in the venom-incubated cultures compared to controls (P<0.001). Results also indicated very significant decreases and parallel equally significant increases in GSH and GSSG levels respectively in the envenomed cultures compared to controls (P<0.001) leading to a drastically lower GSH/GSSG ratio. However, further incubation of the EcV-treated cultures with Asc (400 µM for 12 h) restored the activities and levels of all investigated parameters including the expression levels of the antioxidant genes to control venom-free values. It is concluded that Asc acted to neutralize the increased reactive oxygen species generation, thus ameliorating the EcV-induced oxidative stress and alleviating the downregulation of antioxidant genes.